2005
DOI: 10.1016/j.psychres.2005.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Offspring from families at high risk for alcohol dependence: Increased body mass index in association with prenatal exposure to cigarettes but not alcohol

Abstract: The prevalence of overweight and obese children is increasing, a tendency that can be expected to increase the risk of adverse outcomes in adulthood. The aim of this study was to determine if prenatal exposure to alcohol, cigarettes, and street drugs would be associated with differences in body mass index (BMI) in childhood and adolescence in offspring from families at high and low genetic risk for developing alcohol dependence. Annual follow-up of offspring (N =288) provided 1200 height and weight assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…Somm et al [9] showed in a recent publication that prenatal nicotine exposure caused alterations in pancreatic islet development, which can lead to the metabolic syndrome in offspring with early signs of adipose tissue dysregulation. These results suggest a direct association between maternal nicotine consumption and the impaired control of body weight and glucose metabolism in neonates [10] . Nicotine also causes neurotoxic effects that can potentially contribute to abnormalities in synaptic activity [3] and damage the central nervous system of the child [11] .…”
Section: Introductionmentioning
confidence: 71%
“…Somm et al [9] showed in a recent publication that prenatal nicotine exposure caused alterations in pancreatic islet development, which can lead to the metabolic syndrome in offspring with early signs of adipose tissue dysregulation. These results suggest a direct association between maternal nicotine consumption and the impaired control of body weight and glucose metabolism in neonates [10] . Nicotine also causes neurotoxic effects that can potentially contribute to abnormalities in synaptic activity [3] and damage the central nervous system of the child [11] .…”
Section: Introductionmentioning
confidence: 71%
“…Environmental estrogens such as bisphenol A and nonylphenol, for instance, can promote adipocyte differentiation or proliferation in murine cell lines (70,71). Furthermore, epidemiological studies link maternal smoking during pregnancy to an elevated risk of childhood obesity (72)(73)(74)(75)(76).…”
Section: Discussionmentioning
confidence: 99%
“…Also tobacco exposure can contribute to obesity development since several epidemiological studies have reported that maternal smoking during pregnancy and/or lactation can be a risk factor for child and teenager obesity and hypertension (Gao et al, 2005;Goldani et al, 2007;Hill et al, 2005;Von Kries et al, 2002;Wideroe et al, 2003). The relationship between environmental, nutritional and hormonal influences at critical windows of plasticity and several chronic adult diseases is named programming (Barker, 2003;de Moura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%